Self-Esteem and Gender as Correlates of Secondary School Teachers’ Effectiveness in South-West, Nigeria - MELEKEOWEI, Premobowei Dele (Ilorin Journal of Education, 2024)
The teaching profession is an age long discipline that involves interaction between the instructor with one or more students and with the objective of influencing behavioral changes. The teachers’ competence is associated with certain psychological and demographic qualities which have been found to hinder their effectiveness. This study therefore examined the causal linkage between self-esteem, gender and secondary school teachers’ effectiveness in the south west, Nigeria. The survey research design of expost-facto was adopted, whereas, the multistage sampling procedure was used to obtain the sample size of 1650 public secondary school teachers. The instrument used to obtain data for the study comprised of Teacher Effectiveness (r=0.76) and Rosenberg self-esteem (r= 0.73) scale. Pearson product moment correlation was used to establish the relationship between the independent and dependent variables @ 0.05 level of significance. The result indicated that a linear relationship was found between gender (r=0.053) and teacher effectiveness, whereas, an inverse relationship was found between self-esteem (r= -0.017) and teacher effectiveness. The teachers’ gender is a contributing factor towards their effectiveness and this must be integrated into the recruitment process of secondary school teachers’ in southwest, Nigeria.